2021
DOI: 10.24912/jbmi.v4i1.9487
|View full text |Cite
|
Sign up to set email alerts
|

Penyediaan Sarana Cuci Tangan Sederhana Untuk Pencegahan Penyebaran Covid-19 Di Pasar Genteng, Suradita, Cisauk

Abstract: COVID-19, a source of distress in most countries, has encouraged world leaders to issue necessary policies to resolve this global pandemic. An alarming rate of infections in the community has pushed the Indonesian government to come up with the Large-Scale Social Restriction (Pembatasan Sosial Berskala Besar/PSBB). The faculty of Biotechnology of Atma Jaya Catholic University of Indonesia has since initiated a community service to halt the spread of COVID-19 by supplying simple hand washing facilities around P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar findings were in line with this study's results, stating that clean water is odourless, tasteless, and colourless. 2,8,11,12 Handwashing facility is the vital tool expected to increase public awareness about the importance of maintaining personal hygiene to prevent the spread of COVID-19. 11,13 The study results showed that nine out of ten respondents had a handwashing facility and hand sanitizer in their house, which was expected to minimize the transmission of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were in line with this study's results, stating that clean water is odourless, tasteless, and colourless. 2,8,11,12 Handwashing facility is the vital tool expected to increase public awareness about the importance of maintaining personal hygiene to prevent the spread of COVID-19. 11,13 The study results showed that nine out of ten respondents had a handwashing facility and hand sanitizer in their house, which was expected to minimize the transmission of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,11,12 Handwashing facility is the vital tool expected to increase public awareness about the importance of maintaining personal hygiene to prevent the spread of COVID-19. 11,13 The study results showed that nine out of ten respondents had a handwashing facility and hand sanitizer in their house, which was expected to minimize the transmission of COVID-19. Hands are a part of the body that is easily contaminated with dirt and germs, where when we hold an object or shake hands, the germs are attached to the skin of the hands.…”
Section: Discussionmentioning
confidence: 99%